“Adapt or Perish”: The uncertain fate of childhood contributory negligence in Scotland - Lesley-Anne Barnes Macfarlane (De Jure, 2023)
The field of Delict (Tort) is a noteworthy exception to widespread, evolving child rights-based norms across Scottish Law, for there has been little change in the treatment of children in Delict in Scotland in over a century. This article argues that childhood contributory negligence, in its current form, cannot survive imminent, and full, statutory incorporation of the CRC in Scotland. The framework and operation of the law governing childhood contributory negligence is critically reviewed, drawing on Scottish, and relevant UK-wide, case law. Widespread inconsistencies in judicial reasoning about children in contributory negligence deter-minations are highlighted. Thereafter, consideration is given to what CRC compliance might involve in the field of Delict. Two core rights, article 3 (best interests) and article 6 (child’s right to life, survival and development), are then discussed with reference to new Scottish Criminal Sentencing guideline requiring courts to consider the evolving capacity of young people up until the age of 25 years. The article concludes with a call for conceptual and practical reform so that the largely punitive regime of childhood contributory negligence in Scotland must now - in the words of H.G. Wells - either “adapt or perish”.